Increased Adoption of Quality Improvement Interventions to Implement Evidence‐Based Practices for Pressure Ulcer Prevention in U.S. Academic Medical Centers. Issue 6 (13th October 2015) - Padula, William V.; Mishra, Manish K.; Makic, Mary Beth F.; Wald, Heidi L.; Campbell, Jonathan D.; Nair, Kavita V.; Valuck, Robert J.
ABSTRACT: Objective: In 2008, the U.S. Centers for Medicare and Medicaid Services enacted a nonpayment policy for stage III and IV hospital‐acquired pressure ulcers (HAPUs), which incentivized hospitals to improve prevention efforts. In response, hospitals looked for ways to support implementation of evidence‐based practices for HAPU prevention, such as adoption of quality improvement (QI) interventions. The objective of this study was to quantify adoption patterns of QI interventions for supporting evidence‐based practices for HAPU prevention. Methods: This study surveyed wound care specialists working at hospitals within the University HealthSystem Consortium. A questionnaire was used to retrospectively describe QI adoption patterns according to 25 HAPU‐specific QI interventions into four domains: leadership, staff, information technology (IT), and performance and improvement. Respondents indicated QI interventions implemented between 2007 and 2012 to the nearest quarter and year. Descriptive statistics defined patterns of QI adoption. A t ‐test and statistical process control chart established statistically significant increase in adoption following nonpayment policy enactment in October 2008. Increase are described in terms of scope (number of QI domains employed) and scale (number of QI interventions within domains). Results: Fifty‐three of the 55 hospitals surveyed reported implementing QI interventions for HAPU prevention. Leadership interventions were most frequent, increasing in scope from 40% to 63% between 2008 and 2012; "annual programs to promote pressure ulcer prevention" showed the greatest increase in scale. Staff interventions increased in scope from 32% to 53%; "frequent consult driven huddles" showed the greatest increase in scale. IT interventions increased in scope from 31% to 55%. Performance and improvement interventions increased in scope from 18% to 40%, with "new skin care products . . ." increasing the most. Linking Evidence to Action: Academic medical centers increased adoption of QI interventions following changes in nonpayment policy. These QI interventions supported adherence to implementation of pressure ulcer prevention protocols. Changes in payment policies for prevention are effective in QI efforts.